The Exploration of Undergraduate Attitudes and Knowledge about International Agricultural Issues and US Agricultural Policy - Caitlin Bletscher; Megan Gould; Shuyang Qu (Journal of International Agricultural and Extension Education, 2022)
In today’s globalized world, educators and employers generally agree on the necessity for undergraduate agricultural [ag] students to develop a sound understanding of global ag issues and policy. Because of this, many U.S. universities have promoted internationalizing curriculum and increased international study abroad experiences. However, few studies have examined the impact of international experiences on students’ knowledge and attitudes about international ag issues and policies. This study bridges this gap by identifying the relationship between student knowledge and attitude toward international ag issues and U.S. ag policy, and how international experience and demographic variables play a role in that relationship. Adapted from previous literature, an online survey was developed in 2019 among 196 undergraduate students in ag and non-ag fields to measure student knowledge (global aptitude assessment) and student attitude (attitude index score) towards the importance of global agricultural issues and policy. Results concluded that undergraduate students held a low level of knowledge about global ag issues and policy; in fact, ag students held lower average knowledge scores than non-agricultural students. This emphasizes the urgency for administrators to intentionally design and reevaluate our current curriculum to meet these knowledge gaps. Additionally, study abroad experiences did not contribute to students’ knowledge nor attitudes. The authors discuss several possibilities for such results and highlight the call to similarly reevaluate our study abroad curriculum to be more intentional in impacting student knowledge in global ag food systems and acknowledge differences in policy, getting students excited and interested in the global market.
Keywords: agriculture; international agricultural issues; US agricultural policy; undergraduate attitudes; global agriculture